UPAYA PENINGKATAN KOMPETENSI GURU DALAM PROSES PEMBELAJARAN MELALUI SUPERVISI AKADEMIK DI SMA NEGERI 19 BUNGO - zulfahmi zulfahmi (Jurnal Tunas Pendidikan, 2022)
This research is a school action research (PTS) which aims to improve teacher competence in the learning process through academic supervision. PTS is carried out in four stages, namely planning, implementation, observation and reflection. These four activities take place repeatedly in the form of cycles. The subjects of this study were 7 teachers of SMAN 19 Bungo who met the criteria and needed to be given guidance through academic supervision. Data collection techniques were carried out by observation, literature study, and documentation. Direct observation to measure teacher competence in developing lesson plans and implementing classroom learning. The results of teacher competence in the first cycle of 74.1 increased to 86 in the second cycle. So it can be concluded that the competence of teachers in the learning process has increased through the application of academic supervision.